Innovative approaches to the development of the lexical composition of the oil and gas industry : Инновационные подходы развития лексического состава нефтегазовой промышленности (Journal of the College of Languages (JCL), 2022)
The present study discusses one of the most relevant and required topics in the recent period during globalization, the modern Russian system of terms for the oil and gas industry as a whole acquired a complete form in the second half of the twentieth century. The period of the late XX - early XXI centuries. marked by cardinal transformations in all areas of the political, economic, social and cultural life of Russia. These changes could not but affect industrial production. Transition to a new vector of development of the Russian economy based on the development of commercial trade, on the change and improvement of the development of industrial enterprises in the context of the implementation of national projects and the introduction of innovative technologies, on the processes of integration into the world economy, is also typical for the oil and gas industry of the Russian Federation. In addition, under the influence of extra linguistic factors, the terminological sphere also undergoes certain transformations.Аннотация     Данная статья посвящена одной из найболее актуальных и требуемых тем в новейший период во время глоболезации , где современная русская лексическая система нефтегазовой промышленности в целом приобрела законченный вид во второй половине ХХ века. Период конца ХХ – начала ХХI вв. ознаменовался кардинальными трансформациями во всех областях политической, экономической, социальной и культурной жизни России. Эти изменения не могли не затронуть промышленное производство. Переход к новому вектору развития российской экономики, основывающийся на развитии коммерческого товарооборота, на изменении и совершенствовании развития промышленных предприятий в условиях реализации национальных проектов и внедрения инновационных технологий, на процессах интеграции в мировую экономику, характерен и для нефтегазовой промышленности Российской Федерации. Кроме того, под действием экстралингвистических факторов терминологическая сфера также претерпевает определенные трансформации.